2020
DOI: 10.1016/j.euf.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Virus Contamination Through Surgical Smoke During Minimally Invasive Surgery: A Systematic Review of the Literature on a Neglected Issue Revived in the COVID-19 Pandemic Era

Abstract: Context: The coronavirus disease 2019 (COVID-19) pandemic raised concerns about the safety of laparoscopy due to the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diffusion in surgical smoke. Although no case of SARS-CoV-2 contagion related to surgical smoke has been reported, several international surgical societies recommended caution or even discouraged the use of a laparoscopic approach. Objective: To evaluate the risk of virus spread due to surgical smoke during surgical procedures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
2
32
0
1
Order By: Relevance
“…Another limitation is that the particle sizes were appropriate for pathogenic bacteria (eg, 10 microns for Staphylococcus aureus clusters or skin cells carrying bacteria) but larger than some viruses (eg, the minimum studied size of 0.5 microns exceeds the diameter of SARS-CoV-2). 22 However, aerosolized particles in ORs apply to all types of particles (eg, surgical smoke 8 ) and our findings qualitatively applied to all sizes studied ( Tables 1 and 2 ).…”
Section: Discussionsupporting
confidence: 49%
“…Another limitation is that the particle sizes were appropriate for pathogenic bacteria (eg, 10 microns for Staphylococcus aureus clusters or skin cells carrying bacteria) but larger than some viruses (eg, the minimum studied size of 0.5 microns exceeds the diameter of SARS-CoV-2). 22 However, aerosolized particles in ORs apply to all types of particles (eg, surgical smoke 8 ) and our findings qualitatively applied to all sizes studied ( Tables 1 and 2 ).…”
Section: Discussionsupporting
confidence: 49%
“…Zhou et al have demonstrated that the positive rate of HPV DNA in surgical smoke was 29.9% in loop electrosurgical excision procedures [ 24 ], while Kwak et al have reported that the HBV was detected in the surgical smoke in 10 of 11 patients who underwent laparoscopic or robotic surgery [ 8 ]. Even though the SARS-CoV-2 virus has never been found in surgical smoke till date, as its presence has been reported in blood and stools, the risk of viral transmission cannot be excluded [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tokuda et al have described treatment possibilities against surgical smoke and report that the concentration of total volatile organic compounds and formaldehyde could be reduced by using evacuation systems [ 23 ]. Several associations have provided recommendations for laparoscopic surgery, and these include maintaining lower pneumoperitoneum pressure, minimizing the use of energy devices, avoiding long dissecting times, frequent suction to avoid the accumulation of smoke, and safety evacuation before trocar removal or laparotomy [ 24 , 25 ]. In laparoscopic surgery, attention to surgical smoke is important during the extracorporeal procedure performed through a small laparotomy incision.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, considering that the SARS-CoV-2 virus has been identified in blood and stools, the theoretical risk of virus diffusion through surgical smoke cannot be excluded. 30 van Doremalen et al 31 reported that aerosol and fomite transmission of SARS-CoV-2 is possible because the virus can remain viable and infectious in aerosols for several hours and on surfaces for several days. Wang and Du 32 suggested that COVID-19 may be directly transmitted through aerosol, but they concluded that this needs to be further verified by experiments.…”
Section: Discussionmentioning
confidence: 99%